The Relationship of Financial Ratios to Predicting Financial Distress Conditions in the Makmur Farmer Village Unit Cooperative - Bekti Wiji Lestari; Muhammad Safar; Wisang Candra Bintari; Rais Dera Pua Rawi (Peneliti.net, 2023)
This study aims to determine the relationship between financial ratios to predict financial distress in the Koperasi Unit Desa Tani Makmur in Sorong Regency. The method used is non-probability sampling with analysis techniques using statistical analysis with logistic regression testing, correlation, determination and hypothesis testing. The results of this study are Liquidity ratios can be used to predict financial distress in Koperasi Unit Desa Tani Makmur, Solvability ratios can be used to predict financial distress in Koperasi Unit Desa Tani Makmur, Profitability ratios can be used to predict financial distress in Koperasi Unit Desa Tani Makmur, Activity ratios can be used to predict financial distress in Koperasi Unit Desa Tani Makmur.